PELAYANAN PUBLIK PADA SEKSI PENGENDALIAN PERUNTUKAN PENGGUNAAN RUANG DAN KAJIAN LINGKUNGAN HIDUP STRATEGIS (KLHS) DINAS LINGKUNGAN HIDUP DAN KEHUTANAN ACEH - Tasmiati Emsa; Zulfikar Zulfikar (Universitas Jabal Ghafur, 2022)
Public services in the Spatial Utilization Control and Strategic Environmental Assessment (KLHS) Section of the Aceh Environment and Forestry Service in improving services for business actors/and or activities who come to take care of the process of determining environmental permits in the Aceh Environment and the Forestry Service are expected so that Civil Servants Civil servants (PNS) and other employees who are involved in public services in obtaining environmental permits are more focused and professional, so that business actors and/or activities feel satisfied and can work together well so that it is easier to achieve a goal to be achieved together. The research uses a qualitative approach, namely the researcher intends to obtain an indepth description of a social phenomenon related to public services in the Control Section for Spatial Utilization and Strategic Environmental Studies. This study aims to find out and analyze how the Principles of Public Service in the Control Section for Spatial Utilization and Strategic Environmental Studies include the first dimension of simplicity which has two indicators, namely: not convoluted and easy to understand. The second dimension of attitude in service is discipline and courtesy. Then the Public Service Standards in the Spatial Utilization Control and Environmental Study Strategy Section of the Aceh Environment and Forestry Service include the first dimension of service procedures which have two indicators, namely: requirements and inspection while the second dimension is completion time with registration and completion indicators. The results of the study show that public services in the Control Section for Strategic Spatial Utilization and Environmental Studies at the Aceh Environment and Forestry Service are very satisfying in accordance with the recognition of business actors/activities and guaranteed courtesy in their services, hopefully in the future it will be even better.Keywords : Public, Services